A Systematic Approach to Building Content Ecosystems: An End-to-End Perspective from Creation to Distribution - Li, Rui (European Journal of AI, Computing & Informatics, 2026)
Emphasizing an end-to-end perspective from content creation to dispersion, this research article explores a taxonomical coming to building content ecosystem, and by analyzing current methodology and better recitation. This study fundamentally introduces a robust model that incorporate technical promotion and strategical preparation to optimise content ecosystems. Into segment insure the unveiling, literature review, method, answer, treatment, and end, the inquiry is structured, thereby the article include comprehensive data analysis, flowchart, and comparison tables that furnish abstruse brainwave into efficient ecosystem management. On big-scale content initiation, the focussing is, through logistic distribution networks, engage quantitative and qualitative method. Hence to raise content strategy. The determination add by providing actionable solutions for ecosystem development.